Electrocardiographic Changes in Dengue Fever: A Review of Literature - Parchani A; Krishnan VS G; Kumar VS (International Journal of General Medicine, 2021)
Ashwin Parchani,1 Gokul Krishnan VS,2 VK Sunil Kumar3 1Department of Internal Medicine, All India Institute of Medical Sciences, Rishikesh, 249203, India; 2Department of Internal Medicine, Kasturba Medical College, Manipal, 576104, India; 3Consultant Cardiologist, V Care Polyclinic, Dubai, United Arab EmiratesCorrespondence: Gokul Krishnan VSDepartment of Internal Medicine, Kasturba Medical College, Level 3, New OPD Block, Manipal, 576104, IndiaEmail gokulkrishnan8394@gmail.comAbstract: Dengue fever is a prevalent viral disease that primarily affects tropical nations. Although most symptomatic infections have a relatively benign course, a small percentage of patients experience severe clinical symptoms, such as bleeding and endothelial dysfunction, which can lead to hypovolemic shock and cardiovascular collapse. Dengue fever is now known to involve the heart by inducing myocardial inflammation, arrhythmias, and, in rare cases, fulminant myocarditis, up to 13% in severe dengue. Conduction abnormalities can range from benign sinus bradycardia to fulminant tachyarrhythmias and atrioventricular blocks. Although most conduction disturbances are benign and transient, they can occasionally aggravate pre-existing conditions and even be fatal. Unlike other viral myocarditis like hepatitis C induced myocarditis, dengue causes mainly transient changes, and long-term complications like dilated cardiomyopathy are not noted. There is indeed a paucity of data on how to assess and treat individuals with conduction abnormalities. In this review, the authors have discussed the wide variety of conduction abnormalities seen in dengue, their pathophysiology, clinical consequences, and a method for evaluating and managing these individuals.Keywords: Dengue fever, Electrocardiography, Arrhythmia, Myocarditis